Authority of History and Sharah Hadith Thaqalayn (Sunnah Itrah) - Nasrullah, Sanip (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2020)
The Hadith Thaqalayn (al-Qur'an and Ahl al-Bayt) is one of the hadiths which is the central point of the difference in manhaj between Ahl al-Sunnah and Shi'ah. By referring to this hadith, a religious theology according to ahl al-Bayt claimed by the Shi'ah. The thaqalayn hadith is the hadith of Ahl al-Sunnah, one of which was narrated by the Muslim Imam who told that the Prophet had a testament so that Muslims cling to the Qur'an so that they do not get lost. Then the Prophet in the hadith thaqalayn also has a testament so that Muslims always protect the rights of ahl al-Bayt so as not to abuse them. The Shi'ah turns out that when they understand this hadith differently from Ahl al-Sunnah, they argue that the consequence of adhering to thaqalayn is to appoint them as leaders of the ummah because leaders must provide guidance, and ahl al-Bayt is a guide for Muslims. Therefore, by using the library research method (literature study), in this paper we will try to describe the historical authority of several thaqalayn hadiths narrated by the hadith imams, as well as discuss the meaning content of thaqalayn hadith or sunnah itrah by referring to comments the scholars of hadith in the books of rijal and sharah hadith.